1981
DOI: 10.1111/j.1469-8986.1981.tb01832.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Orienting and Startle Blink Modification in Novel and Signal Situations

Abstract: Prior work, has shown that reflex blinking can be facilitated by directing attention to the reflex stimulus. It was assumed that if facilitation were due to sensory enhancement, blinking would also be facilitated by novelty‐induced orienting prior to the reflex‐eliciting stimulus. The assumption was tested by establishing an expectancy for weak tactile stimulation to be followed by an acoustic reflex stimulus and then introducing, without announcement, trials on which weak acoustic or visual stimuli occurred a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 18 publications
1
26
1
Order By: Relevance
“…This is akin to an attentional direction effect, in that response latency was facilitated by the direction of attention to, relative to away from, the eliciting stimulus. Facilitation of startle by directed attention has also been shown in previous research (Bohlin & Graham, 1977;Bohlin, Graham, Silverstein, & Hackley, 1981;.…”
Section: Discussionmentioning
confidence: 79%
“…This is akin to an attentional direction effect, in that response latency was facilitated by the direction of attention to, relative to away from, the eliciting stimulus. Facilitation of startle by directed attention has also been shown in previous research (Bohlin & Graham, 1977;Bohlin, Graham, Silverstein, & Hackley, 1981;.…”
Section: Discussionmentioning
confidence: 79%
“…Examples include, in pigeons, differences in the prestimulus intensity required to elicit the two types of modulation (Stitt, Hoffman, Marsh, & Schwartz, 1976); in rats, magnitude-inhibited but latency-facilitated reflex startle when a reflex stimulus is preceded by two prestimuli at different SOAs, one (64 msec) PPI-eliciting and one (4 msec) latency-facilitating ; similarly, in human adults, a magnitude-reduced reflex whose latency is speeded when a reflex stimulus is preceded by a single 30-to 60-msec prestimulus (Graham, 1980;Graham & Murray, 1977). These and other observations have suggested that latency modulation is mediated by a more direct, i.e., shorter or faster path, than magnitude modulation (Bohlin, Graham, Silverstein, & Hackley, 1981;Graham & Murray, 1977;Hoffman & Ison, 1980).…”
Section: Discussionmentioning
confidence: 83%
“…When the startleeliciting stimulus occurs in the sensory modality that is being attended~e.g., a loud sound while one is listening to music!, startle response magnitude is larger than when attention is focused on a modality other than the one in which the startle is presented~e.g., a loud sound while one is viewing a picture; Bohlin, Graham, Silverstein, & Hackley, 1981!. Although self-focused attention involves drawing attention toward the self and away from the environment, it is unclear whether this phenomenon is functionally equivalent to drawing attention toward one sensory modality and away from another one.…”
Section: The Startle Reflex As a Probe Into Attention And Emotionmentioning
confidence: 98%